Linguistic analysis of discourse in aphasia: A review of the literature. (2nd July 2016) - Bryant, Lucy; Ferguson, Alison; Spencer, Elizabeth
ABSTRACT: This review examined previous research applications of linguistic discourse analysis to assess the language of adults with aphasia. A comprehensive literature search of seven databases identified 165 studies that applied linguistic measures to samples of discourse collected from people with aphasia. Analysis of methodological applications revealed an increase in published research using linguistic discourse analysis over the past 40 years, particularly to measure the generalisation of therapy outcomes to language in use. Narrative language samples were most frequently subject to analysis though all language genres were observed across included studies. A total of 536 different linguistic measures were applied to examine language behaviours. Growth in the research use of linguistic discourse analysis and suggestions that this growth may be reflected in clinical practice requires further investigation. Future research directions are discussed to investigate clinical use of discourse analysis and examine the differences that exist between research and clinical practice.